Forecasting Production Trafo to Get SDOH Using Seasonal ARIMA Method in PT. XYZ - Muhammad Dio Dwi Septian; Tedjo Sukmono (Universitas Muhammadiyah Sidoarjo, 2021)
In the production process at PT. XYZ has a fluctuating data pattern and contains seasonality. This resulted in a reduction in the company's operational efficiency and difficulty in preparing supplies to meet uncertain demand. The method according to the demand pattern at PT. XYZ in this transformer product is the SARIMA method. The results of forecasting on transformer production at PT.XYZ gets the SARIMA(1,0,1)(1,1,1) model with influenced by the results observed at 13 weeks and errors at 14 weeks ago. The results of this forecast are used in determining the safety stock in 2021 with regard to SDOH. The SDOH planning in January 2021 will run out in 30 days with a stock plan of 838 units LV Busing so that a company policy needed to increase or decrease the stock plan if SDOH is below or above 30-35 days.